Recasting HIV/AIDS as a development issue : of rights and resistance - Sobha Raghuram (Technical report series (HIVOS (Organization). South Asia Regional Office) ;, 1997)
Report presents the outcome of two workshops held at Puri in 1994 and Bangalore in 1996; with special reference to India.